2006
DOI: 10.1016/j.cmet.2006.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage insulin receptor deficiency increases ER stress-induced apoptosis and necrotic core formation in advanced atherosclerotic lesions

Abstract: Insulin resistance in diabetes and metabolic syndrome is thought to increase susceptibility to atherosclerotic cardiovascular disease, but the underlying mechanisms are poorly understood. To evaluate the possibility that decreased insulin signaling in macrophage foam cells might worsen atherosclerosis, Ldlr(-/-) mice were transplanted with insulin receptor Insr(+/+) or Insr(-/-) bone marrow. Western diet-fed Insr(-/-) recipients developed larger, more complex lesions with increased necrotic cores and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
263
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 250 publications
(281 citation statements)
references
References 47 publications
13
263
1
4
Order By: Relevance
“…Insulin resistance is known to induce ER stress in monocytes and macrophages (23,24). In this study, we found that diabetic patients demonstrated increased activation of monocyte/macrophage ER stress when compared with controls, regardless of vitamin D status.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Insulin resistance is known to induce ER stress in monocytes and macrophages (23,24). In this study, we found that diabetic patients demonstrated increased activation of monocyte/macrophage ER stress when compared with controls, regardless of vitamin D status.…”
Section: Discussionsupporting
confidence: 50%
“…Interestingly, insulin resistance without hyperglycemia similarly up-regulates adhesion molecules and increases adhesion (21,22). Insulin resistance is also a potent inducer of prolonged endoplasmic reticulum (ER) stress in monocytes and macrophages (23,24). The ER is a dynamic membranous organelle that facilitates correct protein modification, folding, and maturation of proteins.…”
mentioning
confidence: 99%
“…Advanced plaques also contain molecules or conditions that promote calcium-based ER stress, including atherogenic lipoproteins and peroxynitrite (8,13), and lesional macrophages display multiple markers of UPR activation in vivo (9,10). Moreover, we recently found that the apoptosis pathway described here is enhanced in insulin-resistant macrophages both in vitro and in advanced atherosclerotic lesions, and the advanced lesions of humans with type II diabetes are characterized by increased lesional macrophage death and plaque necrosis (48,49). Thus, PRR-mediated macrophage apoptosis in advanced atherosclerotic lesions may be relevant particularly in the setting of insulin resistance.…”
Section: Discussionmentioning
confidence: 56%
“…Macrophage apoptosis can be induced either by loading with free cholesterol or by uptake of oxLDL (16,31,32). We show that HDL at physiologically relevant concentrations has a potent protective role against macrophage apoptosis induced by either method.…”
Section: Discussionmentioning
confidence: 99%